Evaluación de la adición de 3 niveles (1%,2%,3%) de residuos de pimiento (Capsicum annuum) en cobayos (Cavia porcellus) en la fase de destete al engorde en la Unidad Educativa Simón Rodríguez - Flores Orbe, Jessica Alejandra (2016)
This research was conducted in Cotopaxi province, Latacunga Canton, Alaquez Parish. The main objective of this research was to evaluate the addition of pepper residues (Capsicum annuum) 1% - 2% - 3% as a food supplement for guinea pig (Cavia porcellus) to promote growth, determining its influence on the productive variables such as weight gain, feed intake ( alfalfa forage + pepper residues), feed conversion, mortality, cost - benefit. Design of randomized complete was handled, for which four treatments resulting from the combination of two raw materials, explained in detail below: Treatment 1 (1% pepper residues + 99% alfalfa forage); Treatment 2 (2% residues pepper + 98% forage alfalfa); Treatment 3 (3% pepper residues + 97% forage alfalfa) and Treatment 4 (100% alfalfa forage as control treatment). For the experiment 40 male guinea pigs were used uncastrated weaned between 15 and 21 days. They were divided into four treatments with 10 guinea pigs each....